Influence of muscle mass in the assessment of lower limb strength in COPD: validation of the prediction equation. Issue 6 (2nd September 2017) - Trethewey, Ruth; Esliger, Dale; Petherick, Emily; Evans, Rachael; Greening, Neil; James, Benjamin; Kingsnorth, Andrew; Morgan, Mike; Orme, Mark; Sherar, Lauren; Singh, Sally; Toms, Nicole; et al.
Abstract : Absence of established reference values limits application of quadriceps maximal voluntary contraction (QMVC) measurement. The impact of muscle mass inclusion in predictions is unclear. Prediction equations encompassing gender, age and size with (FFM+) and without (FFM−), derived in healthy adults (n=175), are presented and compared in two COPD cohorts recruited from primary care (COPD-PC, n=112) and a complex care COPD clinic (COPD-CC, n=189). Explained variance was comparable between the prediction models (R2: FFM+: 0.59, FFM−: 0.60) as were per cent predictions in COPD-PC (88.8%, 88.3%). However, fat-free mass inclusion reduced the prevalence of weakness in COPD, particularly in COPD-CC where 11.9% fewer were deemed weak.